2005
DOI: 10.1111/j.1365-2745.2005.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of experimentally buried seed in Vaccinium: relationship to climate, reproductive factors and natural seed banks

Abstract: Summary 1The fleshy fruited species of Vaccinium are known for their spatial dispersal ability but have generally been found to have poor representation in soil seed banks. 2 A buried seed experiment was conducted with 28 species of Vaccinium , in which seed lots were exhumed at intervals for up to 17 years. Mean species seed longevity was 8.65 years. For five species that persisted in soil for 15-17 years, regression indicates survival times of more than 20 years. 3 Climatic factors (particularly annual tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 62 publications
3
31
0
Order By: Relevance
“…Empetrum nigrum though germinates in the field in some years (McGraw and Shaver 1982). Seed bank studies find very low germination percentages of both species when soils are collected in arctic sites (Fox 1983;Archibold 1984;Ebersole 1989;Molau and Larsson 2000;Cooper et al 2004;Hill and Vander Kloet 2005), compared to samples from boreal sites (Jauhiainen 1998;Alsos et al 2003). However, seeds of both species can remain viable in soil for many years (Molau and Larsson 2000;Hill and Vander Kloet 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Empetrum nigrum though germinates in the field in some years (McGraw and Shaver 1982). Seed bank studies find very low germination percentages of both species when soils are collected in arctic sites (Fox 1983;Archibold 1984;Ebersole 1989;Molau and Larsson 2000;Cooper et al 2004;Hill and Vander Kloet 2005), compared to samples from boreal sites (Jauhiainen 1998;Alsos et al 2003). However, seeds of both species can remain viable in soil for many years (Molau and Larsson 2000;Hill and Vander Kloet 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In vascular plants, Vaccinium spp. buried seed can have a mean longevity of 8.5 years [29], while Artemisia tridentata seed burial augments its short term longevity [30]. This longevity can explain the persistence of the bryophyte soilburied propagule bank in the period studied.…”
Section: Discussionmentioning
confidence: 89%
“…They have suggested that the lack of Vaccinium seeds in the soil cores may be due to fruit being eaten by birds or destroyed by fungal rot, but it is also possible that seed deposits were rare and the cores sampled had no Vaccinium seeds to begin with. Hill and Vander Kloet (2005) found that experimentally buried Vaccinium seed from Nova Scotia had an average longevity of 8.65 years, but some survived the entire 17 years of the study. Regression values suggested that the seed had the potential to survive over 20 years.…”
Section: Reproductionmentioning
confidence: 96%